Dopamine D(2/3) Receptor Availabilities and Evoked Dopamine Release in Striatum Differentially Predict Impulsivity and Novelty Preference in Roman High- and Low-Avoidance Rats - Bellés, Lidia (Int J Neuropsychopharmacol, 2020)
BACKGROUND: Impulsivity and novelty preference are both associated with an increased propensity to develop addiction-like behaviors, but their relationship and respective underlying dopamine (DA) underpinnings are not fully elucidated. METHODS: We evaluated a large cohort (n = 49) of Roman high- and low-avoidance rats using single photon emission computed tomography to concurrently measure in vivo striatal D(2/3) receptor (D(2/3)R) availability and amphetamine (AMPH)-induced DA release in relation to impulsivity and novelty preference using a within-subject design. To further examine the DA-dependent processes related to these traits, midbrain D(2/3)-autoreceptor levels were measured using ex vivo autoradiography in the same animals. RESULTS: We replicated a robust inverse relationship between impulsivity, as measured with the 5-choice serial reaction time task, and D(2/3)R availability in ventral striatum and extended this relationship to D(2/3)R levels measured in dorsal striatum. Novelty preference was positively related to impulsivity and showed inverse associations with D(2/3)R availability in dorsal striatum and ventral striatum. A high magnitude of AMPH-induced DA release in striatum predicted both impulsivity and novelty preference, perhaps owing to the diminished midbrain D(2/3)-autoreceptor availability measured in high-impulsive/novelty-preferring Roman high-avoidance animals that may amplify AMPH effect on DA transmission. Mediation analyses revealed that while D(2/3)R availability and AMPH-induced DA release in striatum are both significant predictors of impulsivity, the effect of striatal D(2/3)R availability on novelty preference is fully mediated by evoked striatal DA release. CONCLUSIONS: Impulsivity and novelty preference are related but mediated by overlapping, yet dissociable, DA-dependent mechanisms in striatum that may interact to promote the emergence of an addiction-prone phenotype.